2002
DOI: 10.1001/archopht.120.8.1063
|View full text |Cite
|
Sign up to set email alerts
|

Angiostatin Inhibits and Regresses Corneal Neovascularization

Abstract: To determine the ability of angiostatin and the angiostatin-producing low-metastatic (LM) clone of Lewis lung carcinoma (LLC) to inhibit and regress corneal neovascularization, as compared with the nonangiostatin-producing high-metastatic (HM) clone. Methods: Three groups of C57BL6/J mice underwent chemical and mechanical denudation of corneal and limbal epithelium. One group remained tumor free while the other 2 were implanted with LLC cells (either the HM or LM clones) subcutaneously the day before, 2 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
5

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 23 publications
(24 reference statements)
0
34
0
5
Order By: Relevance
“…7 Recent studies have shown that angiogenesis inhibitors, such as endostatin, angiostatin, somatostatin, tissue inhibitor of metalloproteinase-3, peptide derived from thrombospondin-1, prolactin and brain-specific angiogenesis inhibitor 1 (BAI1), can inhibit corneal neovascularization and maintain corneal avascularity. [9][10][11][12][13][14][15][16] GA-binding protein (GABP) is a ubiquitously expressed nuclear transcription factor that is involved in a broad range of cellular processes and that regulates target gene expression in the cell cycle and cellular metabolism. 17 GABP is composed of two subunits: GABPa contains the erythroblast transformation-specific DNA-binding domain, whereas the substitutable subunit, GABPb or GABPg, contains ankyrin repeats and the transcriptional activation domain.…”
Section: Introductionmentioning
confidence: 99%
“…7 Recent studies have shown that angiogenesis inhibitors, such as endostatin, angiostatin, somatostatin, tissue inhibitor of metalloproteinase-3, peptide derived from thrombospondin-1, prolactin and brain-specific angiogenesis inhibitor 1 (BAI1), can inhibit corneal neovascularization and maintain corneal avascularity. [9][10][11][12][13][14][15][16] GA-binding protein (GABP) is a ubiquitously expressed nuclear transcription factor that is involved in a broad range of cellular processes and that regulates target gene expression in the cell cycle and cellular metabolism. 17 GABP is composed of two subunits: GABPa contains the erythroblast transformation-specific DNA-binding domain, whereas the substitutable subunit, GABPb or GABPg, contains ankyrin repeats and the transcriptional activation domain.…”
Section: Introductionmentioning
confidence: 99%
“…Researches indicated that angiogenesis inhibitors were highly potent in suppressing angiogenesis which could enable the tumor mass to remain in a dormant state [1][2][3][4] and inhibit the development of corneal neovascularization [5][6][7] . Endostatin could cause G(1) cell cycle arrest in endothelial cells, inhibit endothelial cell proliferation and migration, and promote apoptosis [8] .…”
Section: Introductionmentioning
confidence: 99%
“…These include medication, laser photocoagulation, and surgery. Several angiogenesis inhibitors have been identified and tried as medical treatment, including prolactin, 3 endostatin, 7 angiostatin, 8 somatostatin, 9 cyclosporin A, 18 TNP-470, 19 steroids, 20 nonsteroidal antiinflammatory drugs, 21 thalidomide, 22 methotrexate, 23 and culture supernatant of human amniotic cells. 24 Recently, targeted macrophage metalloelastase or angiostatin gene transfer has been tried to halt angiogenesis in a mouse tumor model, 25,26 and naked plasmids have been shown to be taken up by corneal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Recognition of the potential benefits of controlling angiogenesis has led to a search for angiogenesis inhibitors. 6 Several angiogenesis inhibitors have been identified, such as prolactin, 3 endostatin, 7 angiostatin, 8 somatostatin, 9 and peptide derived from thrombospondin-1 (TSP1), 10 although some of which are the fragments of larger proteins. However, there have been a few studies of gene delivery as a way to reduce neovascularization in the eye.…”
Section: Introductionmentioning
confidence: 99%